2018
DOI: 10.1556/24.61.2018.09
|View full text |Cite
|
Sign up to set email alerts
|

Image processing for fractal geometry-based discrete fracture network modeling input data: A methodological approach

Abstract: With the intent of making data acquisition for fractal geometry-based discrete fracture network (DFN) modeling time-efficient and automatized, a new method was established. For the automation of data retrieval from the images of the studied surfaces, a series of image-processing operations and MATLAB algorithms have been developed. The method allows the retrieval of more than 1,000 fracture-length data/cm2 of one sample in several minutes. This methodology tends to be a useful tool in studies of fracture netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Analysis of the geometric parameters from the prepared specimens should be a straightforward process with not much room for error, and the process remained systematic [13]. This means that fluorescent images were produced in fixed conditions (light, camera settings, possible post processing) before the segmentation to avoid biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the geometric parameters from the prepared specimens should be a straightforward process with not much room for error, and the process remained systematic [13]. This means that fluorescent images were produced in fixed conditions (light, camera settings, possible post processing) before the segmentation to avoid biases.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the microfracture geometry can be achieved by modelling the fracture system's characteristic geometric data: interconnectivity, openness, and density of the microfracture systems. There are three major approaches to modelling the hydraulic properties: An (1) equivalent continuum, (2) DFN, or (3) hybrid models combining an equivalent continuum and DFN [5,[11][12][13].…”
Section: Fracture Network Simulationmentioning
confidence: 99%
“…In recent years, interactive (supervised) machine learning algorithms like the RF classifier (Ho 1994;Breiman 2001; e.g., implemented in the Trainable Weka Segmentation, TWS: Arganda-Carreras et al 2017 or in the opensource software package Ilastik by Berg et al 2019) were primarily developed for biological cases (Babel et al 2020;Brady et al 2020;Eyolfson et al 2020) and offer an alternative to deep learning methods. Berg et al (2018) showed that depending on the training, the RF classifier performs better than the classical segmentation methods and does not require any prior filtering (Garfi et al 2020;Kovács et al 2019;Scanziani et al 2018). The drawbacks of the TWS implementation include high computational demands and the variety of available filters and classifiers, which makes it difficult to implement without sufficient resources and advanced knowledge of the methods.…”
Section: Introductionmentioning
confidence: 99%